EAST GERMAN WRITERS, THE PUBLIC SPHERE, AND THE 1956 WRITERS' CONGRESS. (3rd January 2018) - Brockmann, Stephen
ABSTRACT: This article examines the debates surrounding the 1956 Writers' Congress in East Germany as part of a complex and conflicted process of negotiation and contestation between writers, institutions, the East German government, and the Socialist Unity Party (SED) in a year that witnessed, initially, widespread efforts at liberalisation in much of the socialist world (the USSR, Poland, and Hungary, as well as the GDR) and, subsequently, a crackdown on dissent (especially in Hungary and the GDR). The article shows that there was considerable dispute in the run‐up to the congress, as well as during the congress itself and in its aftermath. The goal is to demonstrate that the 1956 Writers' Congress was more contested than is sometimes believed, and that, on a larger scale, East German literary life in the 1950s was less conformist than its critics have sometimes claimed.